المسؤولية الاجتماعية وأثرها على الاداء المالي لمصرف الوحدة ادارة فروع طرابلس (Comprehensive Journal of Science, 2025)
This study  investigates the impact of the dimensions of corporate social responsibility- employees , customers, community , and environment- on the financial performance of Wahda Bank , Tripoli Branch Management. To achieve the study's objectives , a descriptive – analytical approach was employed , using a questionnaire as the primary tool for data collection . the collected data were statistically analyzed using  SPSS to interpret respondents perceptions . The findings reveal that corporate social responsibility , across its four dimensions , has a statistically significant effect on the financial performance of Wahda Bank . These results underscore the importance of integrating social responsibility practices into the banks strategic and operational activities to enhance its financial outcomes.
Keywords: Social Responsibility, Financial Performance